Diagnostic Accuracy of Sonoelastography in Differential Diagnosis of Benign and Malignant Thyroid Nodules Keeping FNAC as Gold Standard - Tirmizi, Syeda Maryam; Muhammad Nafees; Taqi, Irum; Younas, Rabia (Indus Journal of Bioscience Research, 2025)
Background: Thyroid nodules are not uncommon with a minimal percentage of these nodules malignant. The gold standard in diagnosis is the fine-needle aspiration cytology (FNAC) which is invasive and resource-intensive in low-resourced settings. Strain sonoelastography is a non-invasive technique that can be used to evaluate the stiffness of nodules and distinguish between benign and malignant lesions. This study was done to establish the diagnostic accuracy of strain ultrasound elastography (Tsukuba scoring) in diagnosing benign and malignant thyroid nodules and using FNAC as the reference value. Methodology: This cross-sectional validation study was performed at Department of Radiology, PAF Hospital, Islamabad from 1st October 2023 to September 2024. A total of 258 patients were enrolled for this study using non-probability, consecutive sampling technique. Patients with thyroid nodules that were palpable were subject to strain elastography on a linear probe of 7.5 MHz; a Tsukuba score 1-2 was considered benign and 4-5 malignant. FNAC was done on the nodules which appeared suspicious and compared the results. The calculation of the diagnostic performance (sensitivity, specificity, PPV, NPV, accuracy) and ROC analysis was done with the help of SPSS 25. Results: In strain ultrasound elastography, 57.4% of nodules were benign and 42.6% were malignant; FNAC had 60.1% benign and 39.9% malignant. The percentages of sensitivity, specificity, PPV, NPV, and diagnostic accuracy were 75.7, 79.4, 70.9 and 83.1, respectively. The ROC analysis revealed that under the curve was 0.794 (95% CI). There was no gender difference in performance, but specificity was better in patients aged ≥40 years (84.0) and with nodules of longer duration (81.9). Conclusion: Strain ultrasound elastography effectively differentiated between benign and malignant thyroid nodules in our local population, utilizing FNAC as the gold standard. Its persistent efficacy with both genders, particularly among older persons and those with prolonged duration of nodules.